Impact of the COVID-19 pandemic on suicide: evidence from South Korea - Dongyoung Kim; Pyoungsik Kim (BMC Public Health)
Abstract Objectives The COVID-19 pandemic led to public health crises beyond the direct casualties from the virus itself. This study assesses the impact of COVID-19 on suicide rates in South Korea, which implemented effective policy interventions against COVID-19 and has one of the highest suicide rates among member states of the Organisation for Economic Co-operation and Development (OECD). Study design A county fixed effects model. Methods We analyze county-level data covering the 2017-2022 period from the National Statistical Office of Korea and use a county fixed effects model. The primary outcome is the suicide rate per 100,000 population. Our main analysis compares pre-pandemic suicide rates (2019) with those during the pandemic (2020-2022) at bimonthly frequency, focusing on the population aged 20-59 years. Results We find that, in contrast to the initial global concerns about potential increases in suicide because of pandemic-related stress, suicide rates significantly decreased during the pandemic. However, this trend was not uniform: young women experienced fluctuating suicide rates, highlighting a demographic-specific impact. The study also finds that both people who died by suicide and people who died of other non-suicide causes were more likely to have a college diploma and were less likely to be married. Additionally, there are mixed results regarding the location of death. Overall, the pandemic appears to have had a complex effect on suicide behaviors in South Korea. Conclusions The findings underscore the need for targeted mental health interventions, especially for vulnerable groups such as young women. The findings also emphasize the importance of considering demographic-specific responses in public health strategies to better address the mental health consequences of large-scale crises.